2012
DOI: 10.1016/j.cbi.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of silibinin in the rat liver

Abstract: The flavonolignan silibinin, which is a mixture of two diastereoisomers, silybin A and silybin B, is a component of the extract obtained from the fruit and seeds of the variegated milk thistle (Silybum marianum (L.) Gaertn. (Asteraceae)), known as silymarin. Among the therapeutic properties credited to silibinin, its antihyperglycaemic action has been extensively explored. Silibinin is structurally related to the flavonoids quercetin and fisetin, which have been previously demonstrated to be very active on liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…On the other hand, there is evidence of antiinflammatory properties of silymarin [24], to which the beneficial impact of this herbal drug on leukocyte counts in the present study can be attributed.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…On the other hand, there is evidence of antiinflammatory properties of silymarin [24], to which the beneficial impact of this herbal drug on leukocyte counts in the present study can be attributed.…”
Section: Discussionmentioning
confidence: 41%
“…However, once the oxidative damage is produced by lead, silymarin is almost unable to reverse its consequences. Silymarin ability to act as cellular antioxidant has been attributed to its various beneficial effects including free radical scavenging, reduction of membrane lipid peroxidation and enhancement of GSH reserves [24].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been confirmed, in a model of perfused rat liver, that the hepatoprotectant actions of silybin are related to decreased membrane lipid peroxidation, reduced free radical release, and restoration of the glutathione levels [55]. In vivo, in rats, silybin treatment, at doses similar to those used in humans, significantly protected against high-fat-induced fatty liver by stabilizing mitochondrial membrane fluidity, reducing serum content of alanine aminotransferase, decreasing hepatic malondialdehyde, and increasing superoxide dismutase and glutathione levels.…”
Section: Discussionmentioning
confidence: 93%
“…This inhibition was proposed to be indirect via interaction with the abundant IMM phospholipid cardiolipin, similar to the doxorubicin-mediated inhibition of the mitochondrial phosphate carrier [16]. The antibiotic gatifloxacin also inhibits mitochondrial pyruvate uptake by renal and hepatic mitochondria [17], and silibinin inhibits the MPC in liver mitochondria [18]. Last, it has been reported that zaprinast, a phosphodiesterase inhibitor, blocks mitochondrial pyruvate transport and decreases pyruvate-stimulated oxygen consumption, with no effect on PDH activity [19].…”
Section: Evidence For a Mitochondrial Pyruvate Transportermentioning
confidence: 99%